Efektivitas Penyuluhan Kesehatan Reproduksi pada Calon Pengantin di Puskesmas Pucang Sewu Surabaya - Riantini Amalia; Pulung Siswantara (Universitas Airlangga, 2018)
Premarital period is the best time to prepare physical, psychological, and social condition. Health check-up program and reproductive health promotion for prospective wives are ways to form the quality of family’s health. The aim of this study is to figure out the difference of knowledge before and after reproductive health promotion for prospective wives. This study was conducted in September 2017 at Puskesmas Pucang Sewu. This study is a quntitative research with cross sectional method with paired t-test. The sample of this study was 32 respondents and were given some questionnaires which provided questions about prospective wives’ knowledge of reproductive health before and after the promotion. The promotion of reproductive health was done to increase their knowledge in terms of nutrition level, reproductive health to prepare the precious generation. This research found thatbefore counseling 62.5% of respondents had less knowledge. It then decreased to 12.5% after counseling. The average value of respondents before counseling was 50.62 and then increased to 66.25 after counseling. The mean value is 15.625 and the p value is 0.031 or α less than 0.05. Thus, there was a significant difference of prospective wives’ knowledge before and after promotion was given. Puskesmas Pucang Sewu is recommended to keep giving the premarital counseling with lectures and frequently asked questions method and using slide show media because it has been proven to improve wives’ knowledge. Beside, it is necessary to implement collaboration of wives’ program holder with nutrition and psycology officer related about promotion materials in order to improve knowledge about nutrition and psycology management at wives’.